Capturing the transient species at the electrode–electrolyte interface by in situ dynamic molecular imaging. Issue 73 (8th August 2016) - Yu, Jiachao; Zhou, Yufan; Hua, Xin; Liu, Songqin; Zhu, Zihua; Yu, Xiao-Ying
Abstract : In situ imaging mass spectrometry captured transient species at the solid electrode and electrolyte interface, revealing more complex interfacial reactions. Abstract : In situ time-resolved identification of interfacial transient reaction species were captured using imaging mass spectrometry, leading to the discovery of more complex elementary electrode reactions and providing an unprecedented understanding of the reaction mechanism on the electrode surface and solid–electrolyte interface using dynamic molecular imaging.